STATISTICAL METHODS OF TECHNICAL CONTROL OF PRODUCTION OF GAS TURBINE ENGINES - Kochergina, Tatiana; Khokholush, Maria; Guseva, Tatiana; Selezneva, Maria (Revista Inclusiones, 2020)
This article is devoted to the organization of technical control at the enterprise of the aviation industry using statistical methods. In the course of the study, the substantiation of the role of instruments for technical control of the quality of products of Aviadetal LLC is being conducted. Based on the conducted research, proposals were developed for improving the technical control toolkit. The purpose of this work is to develop recommendations for improving the organization of technical control using statistical methods.